Indoor balneophototherapy for chronic plaque psoriasis: Abridged Cochrane Review. Issue 1 (2nd December 2020) - Peinemann, Frank; Harari, Marco; Peternel, Sandra; Chan, Thalia; Chan, David; Labeit, Alexander M.; Gambichler, Thilo
Abstract: Artificial exposure to ultraviolet B light (UVB) while soaking in an indoor salt bath, also called balneophototherapy, could simulate the natural exposure to the sun while bathing in the Dead Sea. We aimed to assess the effects of this intervention on patients with chronic plaque psoriasis. We searched CENTRAL, MEDLINE, Embase, and LILACS up to June 2019. We included randomized controlled trials (RCTs). The primary efficacy outcome was psoriasis area and severity index (PASI)‐75 to detect people with a 75% or more reduction in the PASI score from baseline. The primary adverse outcome was treatment‐related adverse events requiring withdrawal. We included eight RCTs (2105 participants; 1976 analyzed). With respect to PASI‐75, two studies found that salt bath + UVB may improve psoriasis when compared to UVB alone (risk ratio 1.71, 95% confidence interval 1.24 to 2.35; 278 participants). With respect to treatment‐related adverse events requiring withdrawal, two other studies found little to no difference when compared to UVB alone (risk ratio 0.96, 95% confidence interval 0.35 to 2.64; 404 participants). Salt bath + UVB could improve psoriasis when compared to UVB alone, though, results are based on a limited number of studies and provide low‐certainty evidence.